2014
DOI: 10.1177/0892705714551591
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extrusion reprocessing on the mechanical, thermal, rheological and morphological properties of nylon 6/talc nanocomposites

Abstract: In this study, the preparation of nylon 6/talc nanocomposites was studied by melt blending in a co-rotating twin-screw extruder having length/diameter ratio of 32:1 at a screw rotation speed of 100 r min À1 . Concentration of nanotalc was varied from 1 phr to 5 phr in nylon 6. The composite samples were subjected to a series of three extrusion cycles, and the effect of reprocessing on the structural properties of materials was investigated. Properties such as mechanical (tensile flexural and impact), thermal (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Insignificant change in T m with recycling process was also reported in other studies. 21,22 However, ÁH m and c altered with the recycling process and the presence of glass-fiber in PBT/PC. The values of the crystallinity for PBT/PC were found to be increasing tendency with recycling process and the values were in the range of 35%-50%.…”
Section: Resultsmentioning
confidence: 98%
“…Insignificant change in T m with recycling process was also reported in other studies. 21,22 However, ÁH m and c altered with the recycling process and the presence of glass-fiber in PBT/PC. The values of the crystallinity for PBT/PC were found to be increasing tendency with recycling process and the values were in the range of 35%-50%.…”
Section: Resultsmentioning
confidence: 98%
“…There was no change in the T m value with recycling number for other polymer blends in the literature. 34 –37…”
Section: Resultsmentioning
confidence: 99%
“…In addition, they demonstrated that fifth-recycled PBT/PC-GF composites could be used as a substitute for virgin PBT/PC. Kadam and Mhaske 25 investigated the effects of reprocessing (three extrusion cycles) on the structural properties of nylon 6/talc nanocomposites. Their results confirmed that on the first extrusion, tensile strength and tensile modulus increased by 36.7% and 169.7%, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature,[ [24][25][26] ] once the composite is produced, it is returned to the cycle by shredding into small pieces or grinding while it is reprocessed. However, since the molten material (in this case) is consolidated and re-molten, some voids occur on the fracture surface of the composite materials, which are increased by increasing the recycling number and weakening the interfacial shear strength between the fiber and the matrix.…”
Section: Introductionmentioning
confidence: 99%